The Missing Market for Work Permits - Lokshin, Michael; Ravallion, Martin (World Bank, Washington, DC, 2019)
Citizens have a right to accept any job offer in their country, but that right is not marketable or automatically extended to foreigners. Yet, some citizens have useful things to do if they could rent out their right-to-work, and there are foreigners who would value the new options for employment. Thus, there is a missing market. A solution is to allow people to rent out their right-to-work for a period of their choice. On the other side of the market, foreigners could purchase time-bound work permits. The market would no longer be missing. This paper formulates and studies this policy proposal.